Bayanko kapit sa patalim - Lino Brocka; Stephan Films; Malaya Films ([Manila] Malaya Films, 1985)
Arturo and his wife, Luz Manalastas, both work in a printing press. After Luz becomes pregnant, Arturo ("Turing") is forced to ask for a raise. When he does so, his boss asks him to sign a waiver stating that he is not part of any Labor Union. Soon after, his friends inform him that they are starting a labor union and that they are inviting him to join them. Because of the waiver, he cannot. He is branded by his mates as a traitor, and is treated badly by them. Soon after, the printing press is closed down, and the hospital where Luz is confined will not let Luz go until Turing comes up with the money to pay them. This leads Turing to pursue a life of crime.
DVD
Philip Salvador, Gina Alajar, Venchito Galvez
Keywords: Feature Films